Assessment of Clinical MRI and Intraoperative Findings in Cases of Anorectal Fistula - Narendra P. Narsingh; Varun Goswami; Ranjana Sharma (Journal of Pharmacy and Bioallied Sciences)
Background: This study aimed to assess the correlation between preoperative magnetic resonance imaging (MRI) findings and intraoperative observations in patients diagnosed with anorectal fistulas and evaluate the diagnostic accuracy of MRI in identifying fistulous tracts, internal openings, and associated complications. Materials and Methods: A prospective study was conducted at Pt. JNM Medical College, Raipur, from April 2018 to September 2019, involving 30 patients diagnosed with anorectal fistulas. Preoperative MRI scans were performed for all patients, and findings were compared with intraoperative observations. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of MRI in detecting internal openings, fistulous tracts, and abscesses were calculated. Results: Among the 30 patients, 26 were male (86.66%) and 4 were female (13.33%), with a mean age of 35.6 years. MRI identified 63.33% of cases as simple fistulas and 36.66% as complex fistulas. The internal opening was most commonly located at the 6 o’clock position (26.66%). MRI findings correlated with intraoperative findings in 86.66% of cases. The sensitivity of MRI was 100% for detecting simple tracts and 80% for detecting abscesses, with discrepancies observed in 13.33% of cases. Conclusion: MRI proved to be a valuable tool in the preoperative evaluation of anorectal fistulas, demonstrating high accuracy in identifying fistulous tracts and associated complications. However, in some cases, intraoperative findings differed from MRI, emphasizing the need for thorough surgical exploration.